An Application of Six Sigma for Improving the Efficiency of Power Supply - Chang-Hsien Hsu; Pei-Shih Chen; Chun-Ming Yang (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Implementing the Six Sigma control method is to use define, measure, analyze, improve and control (DMAIC) framework to improve the process from the beginning, emphasize the process management, reduce the process time, eliminate the defects, and increase the passing rate. The aims of this study is to apply Six Sigma control method with DMAIC framework to shorten the power supply over time in order to enhance the power supply efficiency in T. power company (TPC). The result showed that the power supply over time was reduced from 66% to 30% in the Construction Work Second Section.DOI: http://dx.doi.org/10.11591/telkomnika.v11i10.2910